DEVELOPMENT OF LEARNING MEDIA BASED ON VIDEO AT VOCATIONAL HIGH SCHOOL KARYA GUNA JAKARTA - Adi Tri Tyassmadi; Sugeng Priyanto; Valent Adnandhiya Awalia (Department of Mechanical Engineering Education, 2025)
Learning media continues to develop and become an important component that supports the learning process because it can improve the quality of learning, help increase student engagement, and make lessons more accessible. The utilisation of learning media has some weaknesses such as not being able to display the original movement in practice and less interactive. These weaknesses can be overcome through media customization and development. Quality education can be realized by changing conventional media into learning media that is more appropriate and easier to understand. This study aims to develop and design learning video media for clutch system maintenance subject matter in Light Vehicle Chassis and Powertrain Maintenance subjects according to material experts, media experts, and media feasibility tests on students. This research uses the Research and Development (R&D) method and uses the 4D development model. The results of the feasibility test of video-based learning media resulted 95.29% from material expert validators, 86.66% from media expert validators, and 88% from the results of the media feasibility test results of 30 students. Based on the overall results of the product feasibility test indicate that video-based learning media is considered very feasible for use in learning.